Annotated record of the detailed examination of Mn deposits from DSDP Site 75, Leg 8 (Core 75-9) - J I Tracey; George H Sutton; Wladimir D Nesteroff; J S Galehouse; Christopher C von der Borch; T Moore; J Lipps; Bilal U Haq; Jean-Pierre Beckmann (PANGAEA, 1971)
Site 75 is located 300 miles southeast of the Marquesas Islands; 400 miles south of Site 74. It is the southernmost of the sites along the N-S line drilled during Leg 8 to investigate the east-west trending accumulation of sediments centered about 2°N near 140°W. This site is a replacement for the site at 31°S originally chosen by the JOIDES Pacific Advisory Panel (PAP Site 27). The original site was not drilled since a preliminary R/V Argo SCAN survey indicated insufficient sediment thickness.
Supplement to: Tracey, JI et al. (1971): Site 75. In: Tracey, J.I.Jr.; et al., Initial Reports of the Deep Sea Drilling Project, 8, Initial Reports of the Deep Sea Drilling Project, U.S. Government Printing Office, VIII, 675-709, https://doi.org/10.2973/dsdp.proc.8.110.1971